Circular RNAs in extracellular vesicles: Promising candidate biomarkers for schizophrenia - Guo, Chuang; Lv, Haibing; Bai, Yulong; Guo, Meng; Li, Pengfei; Tong, Shuping; He, Kuanjun (Frontiers in Genetics, 2023)
As one of common and severe mental illnesses, schizophrenia is difficult to be diagnosed exactly. Both its pathogenesis and the causes of its development are still uncertain because of its etiology complexity. At present, the diagnosis of schizophrenia is mainly based on the patient's symptoms and signs, lacking reliable biomarkers that can be used for diagnosis. Circular RNAs in extracellular vesicles (EV circRNAs) can be used as promising candidate biomarkers for schizophrenia and other diseases, for they are not only high stability and disease specificity, but also are rich in contents and easy to be detected. The review is to focus on the research progress of the correlation between circRNAs and schizophrenia, and then to explores the possibility of EV circRNAs as new biomarkers for the schizophrenia diagnosis.